Microporous Frameworks as Promising Platforms for Antibacterial Strategies Against Oral Diseases - Wan, Yao; Xu, Wenzhou; Ren, Xuan; Wang, Yu; Dong, Biao; Wang, Lin (Frontiers in Bioengineering and Biotechnology, 2020)
Nowadays, the heavy burden of oral diseases such as dental caries, periodontitis, endodontic infections, etc. and their consequences on the patients’ quality of life indicate a strong need for developing effective therapies. Bacterial infections played an important role in the field of oral diseases, in-depth insight of such oral diseases have given rise to the demand for antibacterial therapeutic strategies. Recently, microporous frameworks have attracted tremendous interest in antibacterial application due to their well-defined porous structures for drug delivery. In addition, intensive efforts have been made to enhance the antibacterial performance of microporous frameworks, such as ion doping, photosensitizer incorporation as building blocks, and surface modifications. This review article aims on the major recent developments of microporous frameworks for antibacterial applications against oral diseases. The first part of this paper puts concentration on the cutting-edge researches on the versatile antibacterial strategies of microporous materials via drug delivery, inherent activity and structural modification. The second part discusses the antibacterial applications of microporous frameworks against oral diseases. The applications of microporous frameworks not only have promising therapeutic potential to inhibit bacterial plaque-initiated oral infectious diseases, but also have a wide applicability to other biomedical applications.